Memorandum of understanding between Universiti Teknologi MARA and Politeknik Medica Farma Husada Mataram Lombok, Indonesia / Fakulti Pengurusan Maklumat - Universiti Teknologi MARA, Fakulti Pengurusan Maklumat (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Politeknik Medica Farma Husada Mataram will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.